1966
DOI: 10.2307/1933932
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Distribution of Light in the Forest

Abstract: Spectral distributions of shade light between 400 and 740 mm were measured under corn, sugar maple, oaks, pines, and spruce with a portable recording spectrophotometer. Differences were found between hardwoods and softwoods and between clear cloudy days. An energy maximum at 550 nm, a minimum at 670 to 680 nm, and a very high maximum in the near infrared occurred under all species. Four components of light within a plant canopy can be distinguished: both beam solar radiation and diffused sky radiation are tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0
7

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(96 citation statements)
references
References 13 publications
7
82
0
7
Order By: Relevance
“…This aspect of light quality has received much attention. The decline in the red : far-red ratio has long been known and has been linked in numerous studies to aspects of photomorphogenesis (see reviews by Federer and Tanner, 1966;Smith, 1982;Woodward, 1983;Morgan et al, 1985;Endler, 1993). In the present study, we have found that the red : far-red ratio in the canopy is much lower under clear skies (Hertel et al, 2011), indicating a lower photomorphogenical "light quality" (sensu Smith, 1982) than under diffuse conditions.…”
Section: Spectral Effectssupporting
confidence: 57%
See 1 more Smart Citation
“…This aspect of light quality has received much attention. The decline in the red : far-red ratio has long been known and has been linked in numerous studies to aspects of photomorphogenesis (see reviews by Federer and Tanner, 1966;Smith, 1982;Woodward, 1983;Morgan et al, 1985;Endler, 1993). In the present study, we have found that the red : far-red ratio in the canopy is much lower under clear skies (Hertel et al, 2011), indicating a lower photomorphogenical "light quality" (sensu Smith, 1982) than under diffuse conditions.…”
Section: Spectral Effectssupporting
confidence: 57%
“…The diffuse radiation inside a forest canopy includes the fraction scattered by the foliage itself as well as radiation transmitted through the leaves and through the many gaps in the foliage (Muller, 1971;Grant, 1997). Sunflecks -their size, shape, duration and spectral distribution -depend on the orientation and inclination of woody and photosynthesising elements within the forest canopy as well as the position of the sun in the sky (Federer and Tanner, 1966;Norman and Jarvis, 1974;Pearcy, 1990;Chazdon and Pearcy, 1991;Grant, 1997). The way plants respond to sunflecks may vary, and in some shade plants this response (saturation of photosynthesis, stomatal regulation or possibly photo-inhibition) may be crucial to effective gas exchange and photosynthetic production (Sellers, 1985;Leakey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PAR is defined as the rate of electromagnetic radiation received on a surface with wavelengths from 400 to 700 nm, which corresponds to light energy absorbed by photosensitive pigments with units of µmol photons m -2 s -1 (Brooks 1964;Federer and Tanner 1966;Booth 1976). The measurement of PAR under water presents a number of challenges, such as light scattering and attenuation with depth, as well as differences among the spectral responses of different sensor types.…”
mentioning
confidence: 99%
“…A radiação solar que atinge o topo das copas das árvores está bem próxima do infravermelho enquanto a que atinge o piso da floresta é muitas vezes menor em intensidade e qualidade, porque ela foi absorvida pelas ciorofilas das folhas das plantas dos estratos superiores. Federer & Tanner ( 1966) acharam que a variação de luz no piso da floresta depende do índice de área foliar dos estratos supe· ri ores.…”
Section: 0 -Intensidade Luminosaunclassified